Decreased Neisseria gonorrhoeae genotypic diversity following COVID-19 restrictions in Queensland, Australia 2020. (13th April 2023) - Alharbi, Bushra; Jennison, Amy V.; Hicks, Vicki; Whiley, David M.; Sweeney, Emma; Trembizki, Ella
Abstract: We investigated the potential effects of COVID-19 public health restrictions on the prevalence and distribution of Neisseria gonorrhoeae (NG) genotypes in our Queensland isolate population in the first half of the year 2020. A total of 763 NG isolates were genotyped to examine gonococcal strain distribution and prevalence for the first 6 months of 2020, with 1 January 2020 to 31 March 2020 classified as 'pre' COVID-19 restrictions ( n = 463) and 1 April 2020 to 30 June 2020 classified as 'post' COVID-19 restrictions ( n = 300). Genotypes most prevalent 'pre' restrictions remained proportionally high 'post' restrictions, with some significantly increasing 'post' restrictions. However, genotype diversity was significantly reduced 'post' restrictions. Overall, it seems public health restrictions (9–10 weeks) were not sufficient to affect rates of infection or reduce the prevalence of well-established genotypes in our population, potentially due to reduced access to services or health-seeking behaviours.